STEM-Based Project Based Learning Model to Increase Science Process and Creative Thinking Skills of 5th Grade - Lestari, Tri Puji; Sarwi, Sarwi; Sumarti, Sri Susilogati (Journal of Primary Education, 2018)
The background that drives this research is not yet honed the skills of the process of science and creative thinking. The aims of this research is to know the effect of STEM based learning based learning model on science process skill and creative thinking. The study was conducted on the water cycle material and its use. The research method is Quasi Eksperimental Design. The sampling technique is saturated sampling. The data collection tools in the form of observation instruments of science process skill, and instrument of creative thinking. The data were analyzed using independent t-test to test the difference. In testing the increase and effect of using N-gain. The result of the research shows that there is difference of influence of creative thinking skill, this is seen from the average of N-gain pretest and posttest in the students. The findings of the research are the significant increase of creative thinking skills in the experimental class 1. Improving creative thinking skill which in the high category is 23% and the middle category is 77%. In the experiment class 2, the high category is calculated as 4% and 96% are categorized into the medium category. The conclusion of the research is the learning model of learning based project based learning STEM can improve the skills of science process and creative thinking of the students. Learning based project based learning STEM is expected to be a reference in the application of learning.